Luminescent mesoporous silica nanohybrid based on drug derivative terbium complex - Maturi, Fernando E. [UNESP] (2019)
Mesoporous silica nanoparticles prepared by organic template-driven synthesis have been successfully explored as carriers of the drug-derivate green luminescent complex of terbium (III) with the nonsteroidal anti-inflammatory drug ketoprofen. The terbium (III) complex was synthesized by reacting ketoprofen sodium salt with terbium (III) chloride, which was further adsorbed onto the surface of mesoporous nanoparticles with a mean particle size of 47 ± 4 nm and pore size of 11 nm. The incorporation of the complex into mesoporous silica nanoparticles was tracked by the decrease in the surface area and pore size of the nanoparticles, and successfully demonstrated by substantial changes in the adsorption isotherms and thermal and vibrational spectroscopy results. The cytotoxicity assay and confocal microscopy have shown that the novel luminescent nanohybrid presents high cell viability and the characteristic terbium (III) emission can be assessed through two-photon excitation, which paves the way for bioimaging applications in nanomedicine.